Antioxidant and immune responses of common carp (Cyprinus carpio) anesthetized by cineole: Effects of anesthetic concentration - Seyyed Morteza Hoseini (2020)
© 2019 Elsevier B.V. In the present study, the effects of anesthesia with 1,8-cineole (cineole) were investigated on the antioxidant, innate immune and inflammatory responses of common carp (Cyprinus carpio). The anesthetic efficacy of cineole was determined using 200, 400, 600, 800, 1000 and 1200 μl/l concentrations. The results showed that concentrations of 400–1200 μl/l induced all stages of anesthesia in the fish. The time range for stages 1, 2, 3 and 4 were 58.6–13.1, 110–42, 270–80 and 460-140 s, respectively; at cineole concentrations of 400–1200 μl/l. In the second experiment, fish were anesthetized with 400 and 1000 μl/l cineole and were sampled immediately, and again, 24 h after anesthesia. Anesthesia with 400 μl/l cineole led to immediate increase in plasma cortisol and glucose levels. Hepatic SOD, CAT, and GPx activities significantly increased; whereas GSH significantly decreased after anesthesia, depending on both the cineole concentration and sampling time. In general, 1000 μl/l cineole pronounced more significant effects on these parameters, 24 h after anesthesia. Fish hepatic MDA levels presented significant elevation, and both lysozyme and bactericidal activity increased 24 h after anesthesia with 1000 μl/l cineole. The fish anesthetized with 400 μl/l cineole showed immediate, significant increase in plasma bactericidal activity, as well as 24 h after anesthesia. Anesthesia had no significant effects on plasma complement activity. The 400 μl/l cineole significantly down-regulated the gene expression of tnfα and il1β, immediately after the anesthesia. In conclusion, anesthesia with 1000 μl/l cineole proved suitable for rapid sampling, yet not for practical aquaculture. Moreover, anesthesia led to an apparent increase in innate immune responses, which may be a defensive response to anesthesia-induced stress.